Nematicidal potential of Microbacterium maritypicum Sneb159 against Heterodera glycines and the complete genome sequence analysis - Jing Zhao; Jing Zhao; Jing Zhao; Zhifu Xing; Aatika Sikandar; Yuxi Duan (Frontiers in Plant Science)
IntroductionHeterodera glycines is one of the most important pathogens of soybean production worldwide. Biological control provides a strategy for sustainable and environmentally friendly nematode management.MethodsIn this study, solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC-MS) was used to reveal the volatile nematicidal compounds of Microbacterium maritypicum Sneb159 and the mode of action was further elucidated via whole genome sequencing.ResultsThe present study demonstrated that M. maritypicum Sneb159 fermentation broth showed strong nematicidal activities against H. glycines. The filtrate rather than bacterial cells played a role in the nematicidal character, and reduced the invasion number as well as suppressed the development of juveniles in soybean. The analysis of chemotaxis showed that M. maritypicum Sneb159 has a repellent effect on H. glycines in pot experiments. The volatiles produced by M. maritypicum Sneb159 are toxic to H. glycines for both juveniles and eggs. The seven compounds were analyzed using SPME-GC-MS. In the bioassays, dimethyl disulfide and dimethyl trisulfide showed both direct contact and fumigated effect on juveniles and eggs. The complete genome sequence of the bacterium M. maritypicum Sneb159 was completed using the PacBio sequencing platform. The genome comprised 3895529 bp and a 68.63% G + C content. Three secondary metabolites gene clusters were predicted by the antiSMASH system.DiscussionThe findings reveal multifunction of M. maritypicum Sneb159 towards H. glycines, and has the potential to be developed as a safe nematicidal agent.